2019
DOI: 10.3389/fnins.2019.00165
|View full text |Cite
|
Sign up to set email alerts
|

Iron Metabolism of the Skeletal Muscle and Neurodegeneration

Abstract: Recent studies clearly indicate that the endocrine function of the skeletal muscle is essential for a long and healthy life. Regular exercise, which has been shown to stimulate the release of myokines, lowers the risk of many diseases, including Alzheimer’s and Parkinson’s disease, emphasizing the role of skeletal muscle in proper functioning of other tissues. In addition, exercise increases insulin sensitivity, which may also impact iron metabolism. Even though the role of iron in neurodegeneration is well es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 154 publications
(172 reference statements)
1
44
0
1
Order By: Relevance
“…Furthermore, FOXO3a and CAT have apoptosis-regulation properties [28,29]. Recently it has been shown that FOXO3a controls the expression of ferritin and catalase mRNA [30,31], thus the next goal of this study was to determine the effect of training and supplementation on the expression of these genes. Unfortunately, no significant changes were observed for FOXO3a and CAT mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FOXO3a and CAT have apoptosis-regulation properties [28,29]. Recently it has been shown that FOXO3a controls the expression of ferritin and catalase mRNA [30,31], thus the next goal of this study was to determine the effect of training and supplementation on the expression of these genes. Unfortunately, no significant changes were observed for FOXO3a and CAT mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, TNF infusion induces decrement in the left ventricular performance (Pagani et al, 1992). In the skeletal muscle, proinflammatory cytokines induce several deleterious changes, including an increase in oxidative stress activation atrophy, delay in muscle recovery, and many others (Halon-Golabek et al, 2019). In addition, high oxygen demand by the skeletal muscle leads to augmented generation of reactive oxygen species (ROS), which stimulate inflammation (Radak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We identified 13 total co- Intriguingly, PTPN23 and NCOA4, hubs in the SC.M4 and SC.M2 modules respectively, are involved in the autophagy of ferritin 40,41 , which may link iron metabolism and neurodegeneration via these genes' involvement in iron metabolism and ferroptosis 42 . Ferritin has been found to be elevated in serum and cerebrospinal fluid (CSF) from ALS patients [43][44][45] , and recent work implicates iron metabolism in muscle health, suggesting serum ferritin as a potential biomarker in ALS 46 . Based on this, we hypothesize that disruptions in autophagy of ferritin are involved at early stages of ALS pathophysiology.…”
Section: Discussionmentioning
confidence: 99%